Optically pure gamma-butyrolactones and epoxy esters via two stereocentered HKR of 3-substituted epoxy esters: a formal synthesis of (-)-paroxetine, Ro 67-8867 and (+)-eldanolide - Devalankar, Dattatray A.; Karabal, Pratibha U.; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
The HKR of racemic anti- or syn-3-substituted epoxy esters catalyzed by a Co(III)salen complex provides ready access to the corresponding enantioenriched 3,4-disubstituted gamma-butyrolactones and 3-substituted epoxy esters. This strategy has been successfully employed in the formal synthesis of biologically active 3,4-disubstituted piperidine derivatives, (-)-paroxetine and Ro 67-8867 and a natural product, (+)-eldanolide.